MENINGKATKAN PRESTASI PENDIDIKAN AGAMA ISLAM MELALUI PEMBELAJARAN PAIKEM: PEMBELAJARAN AKTIF, INOVATIF, KREATIF, EFEKTIF, MENYENANGKAN - maridjan, sutiah (Jurnal Lingkar Mutu Pendidikan, 2023)
The research was conducted at SMK Negeri 27 Jakarta on even semester, academic year 2022/2023. The research subject was the students of class XI Perhotelan 4, SMK Negeri 27 Jakarta. The research procedure includes some steps, namely, planning, execution, observation, evaluation, and is categorized success if a majority (80%) of studens actively in learning process by using leaning strategy made PAIKEM. In terms of leaning outcomes when 80% of student have got value > 80. Based on the result of action research the PAIKEM learning can increase the activity of student learning. This is shown by the increasing number of student participation in learning. In cycle I, average student activity is 61,58, in cycle II increased to 81,81. The learning PAIKEM average of 67,50 increased to 73,30 after receiving learning PAIKEM in the first cycle, and increased again after improvement of learning in the second cycle into 80,00. Keywords :Improve Achievement of Education, learning of PAIKEM .